The Use of Sustainable Balanced Scorecard for Strategic Planning and Resource Efficiency Improvement based on Supply Chain Performance Measurement and Productivity - Buthaina Rahid Al Kaabi; Bayan Jowmer (International Journal of Supply Chain Management, 2018)
Abstract- Performance assessment of supply chain management can be helpful in managing. One of the new approaches in this area is the use of a balanced scorecard that addresses the supply chain management strategy as a set of essential goals. Balanced Scorecard has no control role and its criteria do not apply to describing past performance. Rather, these criteria are a tool for explaining the organization's strategy and, by integrating and coordinating activities at its various levels, enables the achievement of organizational goals. In this paper, the supply chain literature and performance evaluation of supply chain management have been investigated first. The aim of this study is to establish a sustainable balanced scorecard for the selected population with the inclusion of resources, objectives, indicators, measures, issues and dimensions of the sustainability of Iraqi universities using the philosophy of strategic planning following a scientific and modern manner. Through the diagnosis of strengths and weaknesses following by a proposed treatment, the card is designed to improve the efficiency of the resources at the Faculty of Management and Economics in University of Mustansiriya. The study concludes that what is needed to ensure the assessment of the performance and integration of the dimensions of sustainability no longer in accordance with the modern methods and techniques. Also, the most important of the planning process of the College of Management and Economics is to identify the strength and weakness of their positions and by comparing the actual reality of the quality standards of higher education organizations and improve the efficiency of their resources.